Modelo do potencial ótico complexo para estudo de espalhamento de elétrons por moléculas e radicais livres - Castro, Elisangela Aparecida Y (2008)
In this work, we seek a better understanding of the role of the absorption potential involved in the dynamics of electron-atom (-molecule) interactions, in arder to develop a po¬tential model that better represents the absorption effects in a wide incident energy range. Ideally, this potential should be free of adjustable parameters, and should be able to re¬produce not only the elastic differential, integral and momentum transfer cross sections but algo the gran-total and total absorption cross sections for electron-molecule collision, in a wide incident energy range. A detailed review of the absorption potential models reported in the literature that include "Quasi-Free Scattering Madel" (QFSM) originally proposed by Staszewska et aI. [37], and the modified QFSM versions of Blanco and Garcia [41] was IDade. A comparative study using these potentials was dane through the calculation of various electron scattering cross sections by a group of atoms and molecules, such as Ar, N2, C2H2 and H2O, for which an abundant experimental data is available in the literature. Such studies allowed us to assess the virtues and deficiencies of these models. Afterwards we have proposed a modification in the version 3 of QFSM of Staszewska et aI., based on the quasi- free electron and binary-encounter approximations in arder to generate a potential that better represents the dynamics of electron-target interaction. In our model, an empir¬ical scaling factor tas been proposed ,in, ordeFI,to, eorrect, the I dist0l1tion of the absorption potential caused by the free-electron-gas approximation. This factar uses two parameters which are independent of targets and incident energies, thus being able to be used in a predictive purpose for a general target. We have used this modified potential to calculate the cross section for several electron-atom, -molecule and -radical scattering, at 10 - 1000 eV impact energies. The iterative Schwinger variational method (ISVM) combined with the distorted-wave approximation (DWA) was used to solve the scattering equations. The calculated gran- total and total absorption cross sections allowed an improvement relative to those obtained using the version 3 oÍ' QFBM' oÍ'StaSzewska et al:.) I